Who Files Suit? Legal Mobilization and Torture Violations in Europe. (27th April 2016) - Conant, Lisa
Abstract : The European Court of Human Rights (ECHR) is the most active international court. After decades with few allegations of human rights abuses, the ECHR docket expanded in the 1990s. Paradoxically, long‐standing democracies can have standardized violation rates of the prohibition against torture that compare to transitional democracies that struggle to protect rights. Yet it is implausible that human rights abuses increased or that established democracies engage in more torture than new democracies. Instead variations in legal mobilization generate the surge and puzzling distribution of European judgments. I argue that discrepancies between the incidence of torture and litigation reflect variations in support structures, where declared violations can reflect the level of support that individuals receive in pursuing claims rather than the incidence of torture. This dynamic is most pronounced for foreign nationals, who typically possess fewer resources than citizens to access legal institutions and encounter popular and official hostility. As a result, much European litigation concerning torture in long‐standing democracies is transnational in character.